2012
DOI: 10.1002/mrm.24361
|View full text |Cite
|
Sign up to set email alerts
|

4‐T 7Li 3D MR spectroscopy imaging in the brains of bipolar disorder subjects

Abstract: This work demonstrates the first whole brain “high spatial resolution” 7Li MRSI in bipolar disorder subjects. The in vivo quantification is validated by a phantom containing 5 mM lithium salt using the identical RF sequence and imaging protocol. This study is the first demonstration of the 7Li distribution in the brain of bipolar disorder patients on lithium therapy using a 3D MRSI approach. The results show that brain lithium level is strongly correlated with serum lithium concentration. The brain-to-serum li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
20
0
6

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(29 citation statements)
references
References 21 publications
3
20
0
6
Order By: Relevance
“…Li MRS has been conducted by several groups over the past 20 years, with a wide range of quantitative methods applied (3, 7, 10–12, 14, 15, 17, 19, 26–29). The wider availability of high‐field‐strength clinical scanners (with their potential for better SNR and potentially reduced scan times) has rekindled interest in advancing techniques for measuring 7 Li in vivo.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Li MRS has been conducted by several groups over the past 20 years, with a wide range of quantitative methods applied (3, 7, 10–12, 14, 15, 17, 19, 26–29). The wider availability of high‐field‐strength clinical scanners (with their potential for better SNR and potentially reduced scan times) has rekindled interest in advancing techniques for measuring 7 Li in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…The T 1 relaxation time of 7 Li is central to the acquisition and quantitation of the Li signal; however, to date, in vivo estimates are all either at low field (11, 12) or, in animal models, at ultra high field (6, 11, 12). There is little to guide data collection at 3 T (9), the field strength common to the now widely available multinuclear clinical scanners suited to 7 Li MRS (9, 15, 16). Human group data on 7 Li T 1 have been reported only for small samples of patients, with the measurements in healthy subjects restricted to studies of one or two individuals (17–19).…”
mentioning
confidence: 99%
“…Regionally specific effects of lithium would indicate either that brain regions are differentially sensitive to its effects or that the drug itself is heterogeneously distributed across the brain. Recent advances in multinuclear MRI ( 7 Li-MRI) have permitted the rapid determination of brain lithium distribution in vivo (Smith et al, 2018), demonstrating a heterogeneous distribution of lithium in bipolar disorder, in keeping with previous rodent imaging and human magnetic resonance spectroscopy studies (Lee et al, 2012;Zanni et al, 2017). It would therefore be reasonable to propose that the effects of lithium on white matter integrity relate to its regional concentration and the combination of 7 Li-MRI and dMRI affords the capability to explore this.…”
Section: Introductionmentioning
confidence: 54%
“…Very little work has dealt with correlation between brain Li levels and treatment measures. However, as an indicator of the technique's potential at high field, Lee et al 47 recently demonstrated spatial variations of Li concentration in brain for bipolar patients using 4D 7 Li MRSI at 4 T. Figure 15.3 shows slices, presented as overlays on a 1 H anatomic MRI, from the 7 Li MRSI of a bipolar patient. …”
Section: Mrsmentioning
confidence: 96%